Bridging the gap: pracademics in foreign policy - Murphy, Ann Marie; Fulda, Andreas (Cambridge Journals, 2011)
In his seminal work Bridging the Gap: Theory and Practice in Foreign Policy, Alexander George (1993) lamented the great divide between academia and the foreign policymaking community, arguing that greater interaction between scholars and policymakers would produce better policy. We share George's belief that scholars and practitioners each have much to offer the other. In fact, a wide spectrum of opportunities exists for scholars in the field of political science to engage in meaningful public service that can enhance every aspect of their careers, as well as contribute to international understanding.